2008
DOI: 10.1097/dad.0b013e31817330ff
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous CD30-Positive Epithelioid Angiosarcoma Following Breast-Conserving Therapy and Irradiation: A Potential Diagnostic Pitfall

Abstract: A case of cutaneous epithelioid angiosarcoma with anomalous CD30 expression, occurring after breast-conserving surgery and adjuvant irradiation, is reported. This seems to be the first such case reported. The differential diagnosis of CD30 epithelioid angiosarcoma is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…CD30-positive tumors had no predilection to specific sites or clinical subgroups of AS or EHE (Table 2). Previous to our study, there have been only rare case reports in the literature describing the so-called anomalous expression of CD30 as a diagnostic pitfall in AS 17-19 . Confirming a prior study, we found no CD30 expression in KS 15 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…CD30-positive tumors had no predilection to specific sites or clinical subgroups of AS or EHE (Table 2). Previous to our study, there have been only rare case reports in the literature describing the so-called anomalous expression of CD30 as a diagnostic pitfall in AS 17-19 . Confirming a prior study, we found no CD30 expression in KS 15 .…”
Section: Discussionmentioning
confidence: 60%
“…There are rare instances of variable CD30 expression in benign 15, 16 and neoplastic 15, 17-19 endothelial cells. The role of CD30 antigen in malignant vascular tumors has not as yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sALCL, the CD30 antigen has been identified in various other non-Hodgkin lymphomas (NHL) including hematological malignancies such as diffuse large B-cell lymphoma (DLBCL), T-cell lymphomas (TCL), primary mediastinal lymphoma (PMBL), post-transplant lymphoproliferative disorders (PTLD), enteropathy associated PTCL,cutaneous malignancies such as mycosis fungoides (MF), Sézary syndrome (SS), and lymphatoid papulosis (LyP) (Stein et al, 1982; Jacobsen et al, 2015; Kim et al, 2014; Schwarting et al, 1989). The CD30 antigen also has been identified in non-lymphomatous malignancies like germ cell tumors such as embryonal carcinoma, seminomas, malignant melanomas, neoplasms of mesenchymal origins including leiomyomas, leiomysarcomas, rhabdomyosarcomas, aggressive fibromatoses, fibrosarcomas, synovial sarcomas, giant cell tumors of tendon sheaths, malignant fibrous histiocytomas, osteosarcomas, Ewing’s sarcomas, in a tumor cell subpopulation of malignant schwannomas, in the Schwann cell compartment of ganglioneuromas, and in the myoepithelial compartment of fibroadenomas, inflammatory myofibroblastic tumors, ovarian cancer, mesothelioma, squamous cell carcinoma, triple negative breast cancer, pancreatic cancer, small cell lung cancer, anal cancer, thyroid carcinoma, cutaneous angiosarcoma, and a small subset of undifferentiated nasopharyngeal non-keratinizing carcinoma (Latza et al, 1995; Gopalan et al, 2009; Dürkop et al, 2000; Pallesen and Hamilton-Dutoit, 1988; Polski and Janney, 1999; Lau et al, 2007; Suster et al, 1998; Bode et al, 2011; Hittmair et al, 1996; Sharman et al, 2012; Garcia-Prats et al, 1998; Dunphy, 2000; Aggerholm-Pedersen et al, 2011; Weed and Folpe, 2008; Kneile et al, 2006; Menasce and Eyden, 2005; Mechtersheimer and Moller, 1990; Mariño-Enríquez et al, 2016). Moreover, systemic mastocytosis, which is classified as a myeloid neoplasm, is also known to express CD30 although the clinical data is limited (Borate et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…it is expressed on activated t-and B-cells and is a diagnostic marker of some lymphomas [Hodgkin's lymphoma, Anaplastic large cell lymphoma (AlCl), some B-cell lymphomas]. though not part of standard diagnostic immunohisotchemical analysis for sarcomas, high expression of CD30 has been reported in up to 30% of AS's [2,3,7,8], making this a potential diagnostic pitfall in AS's as well as opening up to potentially new treatment possibilities with targeted therapy using antibody drug conjugates.…”
mentioning
confidence: 99%